Clinical correlation and determination of Dkk-1 andsclerostin levels in patients with rheumatoid arthritis - Aydemir, Zeynep Sarıcan; Akgöl, Gürkan; Gülkesen, Arif; Kaya, Arzu; Kaman, Dilara; Ulusoy, Hasan (My University, 2020)
The aim of this study is to compare serum Sclerostin and Dickkopf-1 (Dkk-1) levels in patients with rheumatoid artrithis (RA) and healty controls to determine their clinical significance in patients with RA. Sixty with RA according to American Collage of Rhematology criteria and at least one year follow up, enrolled in this study and compared thırty healty controls. To evaluate disease activity score 28 (DAS28) was calculated. Physical function capasity (disability) was asssessed with Health Assesment Quastionnarie (HAQ) and Nottingham Health Profile (NHP). Erythrocyte Sedimentation Rate, C Reactive Protein, Rheumatoid Factor and anticyclic citrullinated peptide levels were determined by routine laboratory methods. Serum sclerostin and Dkk-1 levels of the patients with RA and healty controls were measured by ELISA. Radiographic assesment of hands joints was evaluated according to the modified Larsen score. Between patients with RA and healty controls, there was significant difference with respect to the age (respectively p=0.00) and significant difference with respect to gender (p=0.033). Serum sclerostin and dickkopf-1 levels were significantly higher (p=0.002, p=0.049) in patients with RA compared to healty controls. Serum sclerostin and dickkopf-1 levels were doesnt correlated with clinical and laboratory parameters of disease activity. There was no significant correlation between radiological scoring of joint damage and serum sclerostin and dickkopf-1levels (p 0.05). This study shows that Serum sclerostin and dickkopf-1 levels were increased in RA patients in comparison to control group but there was no significant correlation with the disease activity and joint damage. The sample of our study can be enlarged and further studies are required.
Keywords: Genel ve Dahili Tıp; Romatoloji